Know your Bible ; v. 2 a brief introduction to the Bible - Scroggie, William Graham, 1877-1958 (London, UK Pickering and Inglis, 1953)
Contents : v. 2 : Analytical ; the New Testament. Includes index.
First published in 1940 (Dictionary of Scottish church history and theology). 1960 reprint.
Keywords: Bible. N.T. -- introductions